2017
DOI: 10.7554/elife.19848
|View full text |Cite
|
Sign up to set email alerts
|

Transcription leads to pervasive replisome instability in bacteria

Abstract: The canonical model of DNA replication describes a highly-processive and largely continuous process by which the genome is duplicated. This continuous model is based upon in vitro reconstitution and in vivo ensemble experiments. Here, we characterize the replisome-complex stoichiometry and dynamics with single-molecule resolution in bacterial cells. Strikingly, the stoichiometries of the replicative helicase, DNA polymerase, and clamp loader complexes are consistent with the presence of only one active repliso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 58 publications
5
88
0
Order By: Relevance
“…The reasons for the discrepancy between these population and single-cell studies are unknown. In the same single-molecule microscopy study, measurements of the lifetimes of DNA complexes suggest that restart could be as frequent as five times per generation in Bacillus subtilis, as in E. coli (22). This result highlights the importance of replication restart and shows clearly that replication restart most often does not involve homologous recombination, as this frequency would then be incompatible with the viability of recombination mutants.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The reasons for the discrepancy between these population and single-cell studies are unknown. In the same single-molecule microscopy study, measurements of the lifetimes of DNA complexes suggest that restart could be as frequent as five times per generation in Bacillus subtilis, as in E. coli (22). This result highlights the importance of replication restart and shows clearly that replication restart most often does not involve homologous recombination, as this frequency would then be incompatible with the viability of recombination mutants.…”
mentioning
confidence: 80%
“…That study suggested that the range could be around 18 to 25% of the E. coli cells in a population (21). In contrast, direct measurements of helicase stability in the same dnaC2(Ts) mutant by single-molecule microscopy showed that both helicase complexes disassembled within 20 min in 86% of the cells studied (22). The reasons for the discrepancy between these population and single-cell studies are unknown.…”
mentioning
confidence: 98%
“…However, recent findings suggest that the most common cause of replisome stalling in vivo is RNAP (28, 35, 65). The majority of endogenous replication fork stalling detected by various methods is caused by transcription (28, 35).…”
Section: Consequences For Dna Replicationmentioning
confidence: 99%
“…However, recent findings suggest that the most common cause of replisome stalling in vivo is RNAP (28, 35, 65). The majority of endogenous replication fork stalling detected by various methods is caused by transcription (28, 35). However, regardless of the cause, stalled replication forks, in general, are a major problem for growing cells and must be dissolved and restarted in order for replication to be completed and the chromosomes to be segregated into daughter cells.…”
Section: Consequences For Dna Replicationmentioning
confidence: 99%
See 1 more Smart Citation